PROBLEMATIKA POSISI BURUH PADA PERUSAHAAN PAILIT - Tri Budiyono (Faculty of Law, Universitas Diponegoro, 2013)
Abstract The company which is stated in bankruptcy, sometimes have to face crucial problem in accordance with employees’ right to recieve sum of money, which is called normative rights. The Indonesian legal system has protected the employees’ right by classifying the employees’ wage as a privilege debt. However, in empiric manner the employees’ rights are often ignored because another creditors have the right to pay previously than employees. In this condition, employees and their federation try to file the lawsuit in Constitution Court, to cancel the rule that weakens the employees’ normative rights, but unfortunately employees’ effort was fail. Nevertheless, Constitution Court sent ethical messages that is necessary social programs to cover the weakness of the law. Those ethical messages was addresed to the government. According to the ethical messages, the Government should have the improvement of legal rule in order to give a certainty of the employees’ right. Key words : bankruptcy, employee, normative rights, corporation/ employer, privilege right. Abstrak Perusahaan yang dinyatakan pailit, seringkali menghadapi permasalahan krusial dengan para pekerjanya nerkenaan dengan pembayaran hak normatifnya. Sistem hukum Indonesia telah memberikan perlindungan terhadap hak-hak buruh dengan mengklasifikan hak buruh atas pembayaran gajinya sebagai hutang preferen (dengan hak mendahulu). Namun demikian, secara empirik hak buruh tersebut seringkali terabaikan karena kreditor memiliki hak mendahulu yang derajadnya lebih tinggi dibanding dengan hak buruh. Dalam keadaan yang demikian pekerja melalui Federasi Pekerja mengajukan gugatan ke Mahkamah Konstitusi (MK) untuk membatalkan ketentuan hukum dalam UU Kepailitan yang memperlemah posisi buruh, sayangnya gugatan tersebut ditolak. Namun demikian, MK memberikan memberikan perintah etis kepada pemerintah. Perintah etis tersebut pada dasarnya meminta negara untuk mengembangkan ketentuan hukum agar memberikan kepastian terhadap hak-hak pekerja. Kata kunci : pailit, pekerja, hak normatif, perusahaan, hak preferen